Mechanism Design and Mechanical Analysis of Multi-mode Grab Underactuated Hand - Hanlin Sun; Yu Hou (Jixie chuandong)
A multi-mode grab underactuated hand is proposed for the multifunctional requirements of robot end-effector manipulator. Based on the underactuated theory， the manipulator solves the disadvantages of the traditional compound underactuated hand， such as complex structure， many control elements and weak adaptability. The structure and motion process of multi-mode grab underactuated hand are introduced， and the mathematical model of underactuated manipulator is established. According to the geometric relationship of the manipulator motion analysis and adaptability analysis， and the manipulator grab parameters range is solved. Under different grab modes， the manipulator is analyzed respectively， and the virtual work principle is used to calculate the theoretical output force. The simulation results of virtual prototype show that the manipulator does not need to install force sensor and complex control system， and it can realize two grab modes， namely， flat clip and envelope， which verifies the feasibility of the design.